Penerapan Metode Decision Tree Untuk Memprediksi Prestasi Siswa Kelas XII Dilihat dari Nilai Akhir Semester di SMK Negeri 1 Selong Tahun Pelajaran 2017/2018 - Nasution, Martua Hamonangan; Sofyan, Muh. Iqbal (Fakultas Teknik Universitas Hamzanwadi, 2020)
Along with the development of the human mindset, humans begandevelop systems that can help humans in overcoming problems that arise can be solved easily. Decision tree or better known as the decision tree is an implementation of the system that humans develop in finding and making decisions for these problems by comparing various kinds of problems related to these problems and related to education. Education is a conscious and planned effort to realize learning and the learning process so that students can increase the potential needed by themselves. The function of education is very important as one of the factors driving the development of human resources with the aim of increasing the ability of the community to develop science. Thus, the teaching and learning process is one of the determining factors for the success of education in schools, the low quality of education is the result of the low quality of the learning process carried out in schools. On this occasion, the researcher made preparations for the grades of class XII students at SMK Negeri 1 Selong for 2018/2019 school year using RapidMiner as a tool and applying the Decision Tree method to assess student achievement levels as seen from the report card grades. This research is one of the school action research conducted by researchers who conducted this research in order to improve the achievement of students of SMK Negeri 1 Selong.DOI : 10.29408/jit.v3i1.1825